Pelaksanaan Usaha Kesehatan Sekolah di Sekolah Dasar Negeri di Kecamatan Tengaran Kabupaten Semarang - arifiyanto, yusuf dwi; Irsyada, Roas (Universitas Negeri Semarang, 2023)
The aims of this study were (1) to find out the implementation of the management of the School Health Enterprises, (2) to determine the implementation of the Triad of School Health Enterprises, (3) to determine the availability of facilities and infrastructure for the School Health Enterprises. This type of research is quantitative descriptive. with a survey approach model. the population and sample of this study were all public elementary schools in Tengaran sub-district, totaling 10 elementary schools. data collection techniques using observation techniques, documentation, questionnaires. The data obtained were then analyzed using percentage descriptive analysis techniques. The results of the study show that, (1) The implementation of Public Elementary School Health Business Management in Tengaran District is in the very good category with a percentage rate of 94%, (2) Implementation of the Triad of Public Elementary School Health Business in Tengaran District is in the very good category with a percentage rate reaching 86.95%, (3) The availability of facilities and infrastructure for Public Elementary School School Health Businesses in Tengaran District is included in the complete category with a percentage reaching 64.67%. support is complete.